Selective Modification for Red‐Shifted Excitability: A Small Change in Structure, a Huge Change in Photochemistry. Issue 6 (23rd December 2020) - Becker, Yvonne; Roth, Sina; Scheurer, Maximilian; Jakob, Andreas; Gacek, Daniel A.; Walla, Peter J.; Dreuw, Andreas; Wachtveitl, Josef; Heckel, Alexander
Abstract: We developed three bathochromic, green‐light activatable, photolabile protecting groups based on a nitrodibenzofuran (NDBF) core with D‐π‐A push–pull structures. Variation of donor substituents (D) at the favored ring position enabled us to observe their impact on the photolysis quantum yields. Comparing our new azetidinyl‐NDBF (Az‐NDBF) photolabile protecting group with our earlier published DMA‐NDBF, we obtained insight into its excitation‐specific photochemistry. While the "two‐photon‐only" cage DMA‐NDBF was inert against one‐photon excitation (1PE) in the visible spectral range, we were able to efficiently release glutamic acid from azetidinyl‐NDBF with irradiation at 420 and 530 nm. Thus, a minimal change (a cyclization adding only one carbon atom) resulted in a drastically changed photochemical behavior, which enables photolysis in the green part of the spectrum. Abstract : What a difference one atom makes : Azetidine (az) and dimethylamino (DMA) donor moieties differ only by one carbon atom in their molecular formula, but in the present study we observed huge differences in their impact on the photochemistry of D‐π‐A caging groups. Restriction of the degrees of movement freedom—due to the four‐membered ring—leads to a photocage that can be used within the "green gap" for the release of biologically relevant leaving groups (e.g., glutamic acid).